Chemical composition, sources and secondary processes of aerosols in Baoji city of northwest China. (June 2017) - Wang, Y.C.; Huang, R.-J.; Ni, H.Y.; Chen, Y.; Wang, Q.Y.; Li, G.H.; Tie, X.X.; Shen, Z.X.; Huang, Y.; Liu, S.X.; Dong, W.M.; Xue, P.; et al.
Abstract: Particulate air pollution is a severe environmental problem in China, affecting visibility, air quality, climate and human health. However, previous studies focus mainly on large cities such as Beijing, Shanghai, and Guangzhou. In this study, an Aerodyne Aerosol Chemical Speciation Monitor was deployed in Baoji, a middle size inland city in northwest China from 26 February to 27 March 2014. The non-refractory submicron aerosol (NR-PM1 ) was dominated by organics (55%), followed by sulfate (16%), nitrate (15%), ammonium (11%) and chloride (3%). A source apportionment of the organic aerosol (OA) was performed with the Sofi (Source Finder) interface of ME-2 (Multilinear Engine), and six main sources/factors were identified and classified as hydrocarbon-like OA (HOA), cooking OA (COA), biomass burning OA (BBOA), coal combustion OA (CCOA), less oxidized oxygenated OA (LO-OOA) and more oxidized oxygenated OA (MO-OOA), which contributed 20%, 14%, 13%, 9%, 23% and 21% of total OA, respectively. The contribution of secondary components shows increasing trends from clean days to polluted days, indicating the importance of secondary aerosol formation processes in driving particulate air pollution. The formation of LO-OOA and MO-OOA is mainly driven by photochemical reactions, but significantly influenced by aqueous-phase chemistry during periods of low atmospheric oxidative capacity. Highlights: The high NR-PM1 concentration in Baoji emphasizes the heavily polluted air. The secondary aerosol contribution increased from clean to polluted days. The formation of OOAs is influenced by aqueous-phase chemistry.